Sampling-Based Tolerance-Cost Optimization: Automating Least-Cost Tolerance Allocation Through Joint Metaheuristic Optimization and Sampling-Based Tolerance Analysis - Roth, Martin; Wartzack, Sandro (Research in Tolerancing, 2024)
Tolerance allocation is an essential tolerancing activity to assure the manufacturability of the individual parts, their assembly to the final product, and its functionality in use. Design engineers are responsible for assigning the values for all tolerances specified to limit the critical geometrical part variations. The challenge is to allocate them only as tight as necessary but as wide as possible to simultaneously assure high assembly quality and an economic manufacturing process. Over the last decades, tolerance-cost optimization has turned from first ideas into an effective instrument to address both quality and cost aspects by reformulating and automatically solving the tolerance allocation problem as a mathematical optimization problem. This article presents the basics of sampling-based tolerance-cost optimization. It gives detailed insights in the single methods and their interaction and emphasizes the benefits and challenges when incorporating sampling techniques for tolerance analysis in the optimization workflow. It further introduces a solution for considering multiple, interrelated assembly response functions and geometrical part tolerances correlating on feature, part, and assembly level. An exemplary application illustrates the presented aspects and serves as the basis to discuss the current research gaps and future challenges in this research fiel